Study on shock wave characteristics of rock fracturing process induced by high-intensity electric detonation with voltage as variable - Ting WANG; Baisheng NIE; Zhehao ZHANG; Yilan ZHANG; Yaoqian LI; Xianfeng LIU; Peng LIU; Song BAO; Qinjie WANG (Meikuang Anquan)
High strength electric detonation is a new type of fracturing technology that can efficiently reconstruct coal and rock layers structure, improve the efficiency of coalbed methane mining, increase the proportion of clean energy, and help achieve the “dual carbon” goal; the shock wave energy characteristics of Changqing rock induced by high intensity electric detonation under 16 kV and 204 μF conditions were studied by changing the voltage. The experimental results show that the increase of voltage leads to a decrease in the wavefront time of the voltage curve, and the decrease rate decreases with the increase of voltage, which leads to the increase of the amplitude of voltage wave pattern and the discharge power of high-strength electric detonation, and the increase of shock wave intensity; the direction of maximum shock wave vibration velocity is horizontally from the inner surface of the rock to the outer surface of the rock, which is the main propagation direction of vibration; the main frequency of the vibration energy of shock wave is 0-10 Hz, and the energy is mainly distributed in the range of 0-1 000 Hz; the increase in voltage increases the peak amplitude of the shock wave spectrum and the peak particle velocity of the vibration curve. The increase of voltage makes the shock wave produce stronger instantaneous force, and accelerates the transformation of rock internal structure to instability.